PARAMETRIC STUDY OF ZINC OXIDE NANOPARTICLE SYNTHESIS VIA SOL-GEL METHOD - Eka Aptari, Odara
With versatile applications and potential uses, nanotechnology is a technology that are commonly explored and developed. Due to its abundance, low cost, electrical properties, and non-toxic characteristics, zinc oxide (ZnO) nanoparticles are the most commonly used and demanded nanomaterials. It has a crystal structure hexagonal wurtzite and various morphologies of nanorods, nanoflakes, etc. the most method The common way to prepare ZnO nanoparticles is the sol-gel method. Sol-gel method is a method that undergoes hydrolysis, polycondensation, and growth. This study aims to synthesize ZnO nanoparticles with using a chemical method, namely the sol-gel method and to determine the correlation between various parameters of the method with the characteristics of the nanoparticles. This research consists of the synthesis of ZnO nanoparticles through the sol-gel method, characterization, and analysis result data. Variations of the experiments carried out were different types of precursors, concentration and aging time of the sol. The precursors used in the experiment are zinc acetate dihydrate and zinc nitrate dihydrate with their respective concentrations 0.05M and 0.1M. Variations in sol aging time include 24 hours and 48 hours. Morphology ZnO nanoparticles produced varied from irregular to like plate. Based on XRD analysis, the crystallinity of the ZnO nanoparticles obtained has The high crystallinity ranges from 69.7% to 81.7% by size crystals 11.87 nm to 20.11 nm. Crystal size is highly dependent on the type of precursor and crystallinity depend on the type of precursor, concentration and interaction. Index the whiteness of ZnO nanoparticles was also measured and is a very two parameter influencing it is the type of precursor (acetate) and the interaction between the concentrations precursors and the aging time of the sol. Based on DLS analysis, the particle size is nanoparticles highly dependent on precursor concentration and the use of zinc nitrate increases results. This could be due to the resulting lower crystal size Higher surface area allows agglomeration to occur. For To know the size distribution, the polydispersity index of nanoparticles and the aging of the sol were measured for 24 hours gives a more dispersed result. In addition, the morphology of the nanoparticles ZnO varies from plate-like to irregular.